Biyaya ang meron, biyaya ng meron ang pag-iisip nina Ferriols, Marion at San Agustin - Tolentino, Roy Allan B. (Perspective in the Arts and Humanities ASIA (formerly Asian Perspectives in the Arts and Humanities), 2015)
Inspired by both metaphysics and phenomenology, the work of Roque J. Ferriols, SJ, provides a fascinating insight into givenness, which resonates with the work of Jean-Luc Marion. This paper outlines the points of convergence between these two thinkers, especially as regards their readings of Augustine's Confessiones (The Confessions of St. Agustine). For Marion and Ferriols, Augustine's experience is the journey of a creature discovering both the givenness of creation and selfhood as a gift.